Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jhep.2018.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of radiofrequency ablation as first-line therapy for hepatocellular carcinoma less than 3 cm in potentially transplantable patients

Abstract: Background & Aim: Radiofrequency ablation (RFA) is an effective treatment for single hepatocellular carcinoma (HCC) 3cm. Disease recurrence is common, and in some patients will occur outside transplant criteria. We aimed to assess the incidence and risk factors for recurrence beyond Milan criteria (MC) in potentially transplantable patients treated with RFA as first-line therapy.Methods: We performed a retrospective cohort study of potentially transplantable patients with new diagnoses of unifocal HCC 3cm that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
100
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 33 publications
8
100
2
2
Order By: Relevance
“…International practice guidelines for HCC, including those from the American Association for the Study of Liver Diseases and the European Association for the Study of the Liver (EASL) recommend RFA for the treatment of patients with small, early‐stage HCC . However, relatively frequent tumour recurrences after RFA compared to hepatic resection which could limit the therapeutic efficacy of RFA have been reported, and several studies have been conducted to analyse the risk factors and patterns of recurrence after RFA …”
Section: Introductionmentioning
confidence: 99%
“…International practice guidelines for HCC, including those from the American Association for the Study of Liver Diseases and the European Association for the Study of the Liver (EASL) recommend RFA for the treatment of patients with small, early‐stage HCC . However, relatively frequent tumour recurrences after RFA compared to hepatic resection which could limit the therapeutic efficacy of RFA have been reported, and several studies have been conducted to analyse the risk factors and patterns of recurrence after RFA …”
Section: Introductionmentioning
confidence: 99%
“…Thermal ablation (predominantly radiofrequency ablation (RFA) and microwave ablation (MWA)), has shown excellent therapeutic e cacy in hepatocellular carcinoma and is a commonly used therapy following surgery and embolotherapy (transarterial chemoembolization/transarterial embolization, TACE/TAE) [3][4][5]. Considerable studies have shown that RFA can achieve complete necrosis in most lesions smaller than 3 cm in diameter [6,7]. However, for lesions more than 3 cm in diameter, especially for those over 5 cm, complete necrosis cannot be obtained in a minority of patients, even if the procedure is repeated.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal ablation is a minimally invasive method and is widely used as an effective and safe therapy for liver cancer . It was recently shown as an appropriate alternative for patients with lung cancer who refuse surgery or who are at high risk of post‐thoracotomy morbidity .…”
Section: Introductionmentioning
confidence: 99%
“…Thermal ablation is a minimally invasive method and is widely used as an effective and safe therapy for liver cancer. 6 It was recently shown as an appropriate alternative for patients with lung cancer who refuse surgery or who are at high risk of post-thoracotomy morbidity. 7,8 Thermal ablation, including radiofrequency ablation (RFA) and microwave ablation (MWA), has emerged as a promising treatment for unresectable lung cancer, in line with several recent studies on the ablation of lung cancers.…”
Section: Introductionmentioning
confidence: 99%